Instalação de uma microrrede fotovoltaica conectada/isolada com estocagem e monitoramento com controle da carga alimentada - Dias, Ricardo Machado (Universidade do Vale do Rio dos Sinos, 2015)
This work deals with the development and commissioning of a photovoltaic micro-grid 1680 W connected/alone with storage for management and control of a load considered critical. This micro-grid, employing two PV modules technologies, was installed on Renewable Energy Laboratory at Unisinos. The micro-grid panels is composed of two modules, a 1080 W multicrystalline silicon, and a 600 W of monocrystalline silicon. The first is a grid-connected system and the second is a stand-alone system, respectively. The management and control system, called supervisory, monitors and controls the two systems via data acquisition, which has the task of storing the data on a memory card in addition to showing real-time variables involved in the process through a liquid crystal display. Are made analysis of current values and voltages, AC and DC, to determine the input and output power of the equipment involved in the process, as well as variables such as ambient temperatures and PV module and irradiance. The purpose of this study is to prove availability of the system to meet a load that can be considered as a critical process, in order to maintain a constant power to the load. For this, it is necessary that the load is switched between systems connected to the grid and alone, according to the variables analyzed by the data acquisition system. The analyzes of the data are divided into two parts: PV grid-connected and alone system. For each system, the behavior of tension was analyzed, current and power of the PV panels, as well as the behavior of inverters and power storage bank, considering days with clear skies and overcast sky. For clear sky days analyzed, it was injected into the mains 5.8 kWh of energy. The overall efficiency of this system connected, ηs is 9 %. The data acquisition and control system micro-grid was adequate for the purpose of feeding a remaining charging. Whenever, the mains is switched off, the load is automatically directed to the alone system. When the storage capacity of the database reaches 50%, the load is once again powered by the connected system in parallel with the utility grid.
Keywords: Microrrede fotovoltaica; Sistema de aquisição; Sistema de supervisório; PV micro-grid; System acquisition; Supervisory system; ACCNPQ::Engenharias::Engenharia Mecânica